I'm asked to evaluate for $a,b \gt 0$ the integral $$\int^{\pi/2}_0 \frac{1}{a\text{sin}^2x+b\text{cos}^2x}dx.$$

Here's how I go with it:

I factorise the denominator:


Hence, the integral $$\int^{\pi/2}_0 \frac{1}{a\text{sin}^2x+b\text{cos}^2x}dx=\int^{\pi/2}_0\frac{1}{\text{sin}^2x(a+b\text{cotg}^2x)}dx$$

I make a substitution: $u=\text{cotg}x$ $\Rightarrow du=-\frac{1}{\text{sin}^2x}dx$

$\Rightarrow$ $$-\int^{u_{\pi/2}}_{u_0} \frac{1}{a+bu^2}du$$I make a substitution:

$$t=\frac{\sqrt{b}u}{\sqrt{a}} \Rightarrow dt=\frac{\sqrt{b}}{\sqrt{a}}du$$

$\Rightarrow$ $$-\int^{t_{\pi/2}}_{t_0} \frac{\sqrt{a}}{\sqrt{b}(at^2+a)}dt$$





$$\frac{1}{\sqrt{ab}}\Biggl(\text{arctan}(0)-\text{undefined cotg value}\Biggr)$$

I'm getting an undefined value when I evaluate the definite integral since $\text{cotg}(0)$ is undefined?

Am I doing something wrong?

  • $\begingroup$ The problem is you have not changed the limits for your new variable. For another approach, note that $\sin^2\theta=\dfrac{2t}{1+t^2}$ and $\cos^2\theta=\dfrac{1-t^2}{1+t^2},$ where $t=\tan\theta.$ Then use a substitution accordingly :) Also, the usual convention to write trig-functions is to use three letters. $\endgroup$ – Bumblebee Mar 23 at 17:27
  • $\begingroup$ You forgot to change the bounds, after doing your first substitution, you'll get $ \int\limits_{0}^{+\infty}{\frac{\mathrm{d}u}{a+bu^{2}}} $, after doing the second one, you'll get $ \frac{1}{\sqrt{ab}}\int\limits_{0}^{+\infty}{\frac{\mathrm{d}t}{1+t^{2}}}=\frac{\pi}{2\sqrt{ab}} $, assuming $ a $ and $ b $ are different from $ 0 \cdot $ $\endgroup$ – CHAMSI Mar 23 at 17:35
  • $\begingroup$ You did not change the bounds. $\endgroup$ – hamam_Abdallah Mar 23 at 17:39

By the substitution $ u=cotg(x)$, the integral becomes


$$=\frac{1}{a}\int_0^{+\infty}\frac{du}{1+\frac ba u^2}$$

now, put $v=u\sqrt{\frac ba}$

it gives $$\frac{1}{a}\int_0^{+\infty}\frac{\sqrt {\frac ab}dv}{1+v^2}$$


| cite | improve this answer | |


Another way


Let $\sqrt a\tan x=\sqrt b\tan y$

$x=0\implies y=0$ and $x=\dfrac\pi2\implies y=?$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.